Metastatic pancreatic adenocarcinoma presenting as large bowel obstruction: A case report. (January 2023) - Pacheco, Felipe; Luciano, Emmanuel; Hebert, Danielle; Marar, Omar
Abstract: Introduction and importance: The incidence of pancreatic cancer has gradually increased over the past decades. Metastatic pancreatic cancer to the colon is rare with only seven cases reported. Symptomatic metastasis to the colon as the initial presentation of pancreatic adenocarcinoma has only been reported in two occasions prior to this report. Case presentation: In this report, the diagnosis and operative management of a 78-year-old male who presented with three days of obstipation and computed tomography evidence of an annular obstructing mass in the sigmoid colon in addition to a pancreatic body and lesser sac mass involving the gastric antral region. The patient underwent a laparoscopic sigmoidectomy with end colostomy. Pathology revealed metastatic adenocarcinoma of pancreatic origin. The postoperative period was unremarkable, and the patient was referred to medical oncology to pursue further treatment. Clinical discussion: Symptomatic metastasis to the colon as the initial presentation of pancreatic adenocarcinoma is exceedingly rare. To our knowledge, this is the 3rd case to be reported and the second that was located in the sigmoid colon. Conclusion: The presentation of metastatic pancreatic cancer to the colon causing a colonic obstruction is rare but should be considered in cases of atypical synchronic masses in cross-sectional imaging. When metastatic disease is suspected in the sigmoid colon, it is advisable to perform a colostomy instead of an anastomosis to avoid the potential risk of anastomotic leak that could delay the immediate need for systemic therapy. Highlights: Pancreatic cancer metastatic to the colon is rare. 3rd case of symptomatic metastasis to the sigmoid colon as the initial presentation of pancreatic cancer Complete colonic obstruction required emergent surgical intervention.